(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Public opinion is a form of public consciousness that includes hidden or public attitudes to social events, activities of various groups, organizations and individuals; is manifested in approval or condemnation of certain social issues, determines the behavior of individuals, social groups and certain norms in social relations; applies both within society as a whole and within different social groups. The activity and importance of J. f. is determined by the structural nature of society, the level of development of productive forces, culture, democratic legal norms and freedoms. J. f. it is expressed in the election of authorities, mass communication media, population surveys, etc. In Uzbekistan, the Center for the Study of Public Opinion "Social Opinion" was established.